Maturity z matematiky včera a dnes - Tomeček, Ondřej; Šišma, Pavel, 1964-; Masarykova univerzita. Ústav matematiky a statistiky (2013)
Tato bakalářská práce obsahuje řešení a srovnání státních maturitních příkladů základní i vyšší úrovně obtížnosti z roku 2011 a maturitních příkladů zadávaných studentům Purkyňova gymnázia ve Strážnici v letech 1986 a 2011. Jednotlivé komentáře srovnávající obtížnost jsou zaměřeny vždy na určitou skupinu příkladů.
This bachelor's work includes solution and comparison of state maturita examples of higher and basic level of difficultness in 2011 and maturita examples given students of Purkyně Gymnasium in Strážnice in years 1986 and 2011. Each comment comparing difficulty of each example is only focused on certain group of examples.
Vedoucí práce: Pavel Šišma
Bakalářská práce (Bc.)--Masarykova univerzita, Přírodovědecká fakulta, 2013
Keywords: matematika; maturitní otázky -- Česko -- 1986; maturitní zkoušky -- Česko -- 2011; high school equivalency examinations -- Czechia -- 2011; high school equivalency examinations; mathematics; preparation for high school equivalency examinations -- Czechia -- 1986; preparation for high school equivalency examinations; bakalářské práce; bachelor's theses